Exploring the Role of Action Research in Enhancing Quality Management in Teacher Education: A Case Study - Miryala, Naresh Kumar (Journal of Educational Research and Policies, 2024)
The sincere pursuit process called educational research has developed in modern times. Thus, academic research is a systematic activity devoted to discovering and developing well-organized knowledge that always seeks to find or solve a problem. At present, due to the increasing modernization and engineering development in the education system, research has become inevitable in solving operational problems, as well as in the teacher education field, various problems related to teaching and training and action by inventing various developmental approaches in the field of quality management Research. According to Palmer and Johnson (1971), action research is a method of using research for social activities that involve groups of people to solve problems and find root causes, as if the research itself is a part of empowerment and action. This article will explore the inter-dependence of action research and quality management in teacher education.